THE OWN STRESSES INFLUENCE ON SCALE EFFECT IN CONCRETE - Fenko, Aleksey; Yurko, Ilona; Hasenko, Anton; Krupchenko, Oleksandr; Yurko, Pavlo (Academic journal Industrial Machine Building Civil Engineering, 2019)
The experimental technique and the experiment results on the influence of own stresses unevenly distributed over crosssection on materials strength and on scale effect are presented. The reasons for the occurrence and distribution of suchinfluence are analyzed. Based on the experiments results on fragile duralumin samples, the inevitability of influencing onscale effect in concrete during compression stresses, which are caused by unevenly shrinkage over cross section was proved.Possible reasons for the different (sometimes opposing) results of experimental studies of various authors on scale effect inconcrete in compression are explained. The influence of own stresses unevenly distributed over cross section on scale effectin concrete during compression, depending on samples size and concrete age, is analyzed in detail
Keywords: scale effect; own stresses; concrete strength; shrinkage; creep